The role of indicators in policy formulation: The case of maternal and child health care policy in the Philippines - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2016)
The study examines the role of maternal mortality rate (MMR) and infant mortality rate (IMR) in policy formulation in the Philippines, specifically the controversial legislation of Republic Act 1034, otherwise known as "The Responsible Parenthood and Reproductive Health Act of 2012". It involves taking stock and analysis of various Congressional Records and Senate Journals, particularly those relating to House Bill No. 4244 (An Act Providing for a Comprehensive Policy on Responsible Parenthood, Reproductive Health, and Population and Development, and for Other Purposes) and Senate Bill No. 2865 (An Act Providing for a National Policy Reproductive Health and Population and Development), respectively. The findings of the study show that MMR and IMR have political influence on policy formulation.
Keywords: 330; indicators; role of indicators; policy formulation; maternal mortality rate (MMR); infant mortality rate (IMR)